If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 9x = 4ax Solving w + 9x = 4ax Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9x' to each side of the equation. w + 9x + -9x = 4ax + -9x Combine like terms: 9x + -9x = 0 w + 0 = 4ax + -9x w = 4ax + -9x Simplifying w = 4ax + -9x
| (3a+26)+(5a-4)= | | -1/6=5 | | 14-3n=n-1 | | 3(4x-3)=8x-33 | | (8/9)^-3/2 | | -6p=.6 | | 12-3x=(-6x) | | 8-5f+2f+7= | | 77-2X=61-X | | 80=3y+2y+4+5 | | 12cos(4x)=4sin(4x) | | 8x-2-4x=4x-6 | | 45/x-14= | | 1y-1y= | | 7/18 | | 5n+3n+7+8= | | 6x+46=160 | | y-(-1)=5 | | w(xy)= | | -3x+5(-4x-7)=126 | | Ab+c=ba+c | | -2.2b=-7.7 | | 12cosx=4sinx | | 3u^2=45 | | -2.2b=7.7 | | -3m+45-7(m-1)=8m-(5m-9)-6m+8 | | y=-0.60(25)+108 | | L+3w=24 | | 4x+3=11x+2-7x+1 | | 8/w-4= | | (u-7)(u+5)= | | 11=2y-10x |